A Multi-Group-Supporting Policy Hidden Fine-Grained Data Sharing Scheme in 5G-Enabled IoT With Edge Computing - Jiayin Cai; Hongjie Zhang; Zhilin Duo; Xuan Wang; Xingwen Zhao (IEEE Access, 2024)
Relying on the low latency, high reliability, and large bandwidth of 5G networks, the Internet of Things (IoT) can more efficiently promote information interaction and data utilization across remote locations. However, publicly accessible IoT environments involve risks of data and privacy leakage, which threatens the security and feasibility of the cloud-assisted IoT system. Although attribute-based encryption technology provides a fine-grained and secure data sharing solution, it is still challenging to employ dynamic management of multiple groups when device nodes operate cooperatively in dynamic groups. Thus, we propose a dynamic multi-group-supporting policy-hidden secure data sharing scheme in 5G-enabled IoT. Specifically, we exploit a group key management scheme based on the Chinese Remainder Theorem to achieve efficient dynamic group management in IoT and implement concealment of data owners’ access policies to enhance privacy preservation. Moreover, an edge computing layer has been introduced in our 5G-enabled IoT system to entrust decryption to edge servers and cloud servers, thereby mitigating the calculation burden of data users and assisting to fortify resilience against potential collusion attacks. To improve the availability of our system, mechanisms for validating the correctness of the final ciphertext were also incorporated. We further proved the security of the proposed scheme and conducted experimental simulations, which affirm its efficiency and practicability.